MPBEC, a Matlab Program for Biomolecular Electrostatic Calculations - Vergara-Perez, Sandra; Marucho, Marcelo (Computer physics communications, 2016)
One of the most used and efficient approaches to compute electrostatic properties of biological systems is to numerically solve the Poisson–Boltzmann (PB) equation. There are several software packages available that solve the PB equation for molecules in aqueous electrolyte solutions. Most of these software packages are useful for scientists with specialized training and expertise in computational biophysics. However, the user is usually required to manually take several important choices, depending on the complexity of the biological system, to successfully obtain the numerical solution of the PB equation. This may become an obstacle for researchers, experimentalists, even students with no special training in computational methodologies. Aiming to overcome this limitation, in this article we present MPBEC, a free, cross-platform, open-source software that provides non-experts in the field an easy and efficient way to perform biomolecular electrostatic calculations on single processor computers. MPBEC is a Matlab script based on the Adaptative Poisson–Boltzmann Solver, one of the most popular approaches used to solve the PB equation. MPBEC does not require any user programming, text editing or extensive statistical skills, and comes with detailed user-guide documentation. As a unique feature, MPBEC includes a useful graphical user interface (GUI) application which helps and guides users to configure and setup the optimal parameters and approximations to successfully perform the required biomolecular electrostatic calculations. The GUI also incorporates visualization tools to facilitate users pre- and post-analysis of structural and electrical properties of biomolecules. Program title: MPBEC Catalogue identifier: AEXW_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEXW_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: UTSA license No. of lines in distributed program, including test data, etc.: 1505214 No. of bytes in distributed program, including test data, etc.: 115585507 Distribution format: tar.gz Programming language: Matlab R2010a and higher versions. Computer: Any computer at least with 2.5 GHz speed. Operating system: Windows, Linux Fedora, and Mac OSX. RAM: At least 2 GB of free memory. Classification: 3, 10. External routines: Java, Jmol, pdb2pqr, Propka. Nature of problem: Numerical solution of the linearized PB equation. Solution method: MPBEC uses sparse matrix calculations and iterative linear solvers (gmres, minres, and bicgstab) to solve the discretized (box method) linear PB equation. The stability and the convergence of these iterative solvers are improved by using the incomplete LU factorization which generates pre-conditioner matrices L (lower triangular matrix) and U (upper triangular matrix) at low computational cost. Unusual features: MPBEC incorporates a GUI to provide non-experts in computational biophysics a user-friendly and intuitive tool to obtain biomolecular electrostatic calculations. The GUI provides helpful information about how to fill out the input data by moving the mouse pointer over the corresponding text or blank box. The GUI tests all the input data before running MPBEC to make sure that the solver is properly configured and facilitates the user with the pre- and post-analysis of the biomolecular calculations. Additional comments: MPBEC checks available and required RAM memory before allocation to alert users when the available RAM memory is insufficient to perform the required calculations depending basically on the number of grid points and the size and number of atoms of the biomolecule(s). Therefore, MPBEC might be used with lower RAM memory and processor speed conditions than those mentioned above. The distribution file for this program is over 115 Mbytes and therefore is not delivered directly when download or Email is requested. Instead a html file giving details of how the program can be obtained is sent. Running time: The software runs on single processor computers at low-to-moderate computational cost depending on the computer performance, the biomolecule size, the grid resolution, and required calculations.